Performance Improvement of f-OFDM Systems Using a Concatenated RS/LDPC Coding Scheme - Ghasan Ali Hussain (Journal of Technology and System Information, 2026)
In wireless communication systems, transmission errors are inevitably generated due to interference and fading. Therefore, various approaches have been developed to enhance system reliability, including increasing the transmitted signal power and utilizing error detection and correction schemes. Among these approaches, channel coding is an important technique for reducing the Bit Error Rate (BER). Although LDPC codes are widely adopted in 5G wireless communication systems; achieving ultra-low BER values remains challenging in LDPC codes due to the error-floor phenomenon. To address this limitation, a modified concatenated RS/LDPC code is proposed for an f-OFDM system in this paper. It employs RS codes with LDPC codes followed by an interleaver. Unlike the conventional concatenated RS/LDPC codes that separated both codes by an interleaver. Simulation results demonstrate that the suggested system achieves superior BER performance compared with the conventional concatenated scheme and standalone RS and LDPC codes under both BPSK and QPSK. Furthermore, the suggested f-OFDM system provides superior Out-of-Band Emission (OOBE) suppression compared with the conventional OFDM system, while maintaining a Peak-to-Average Power Ratio (PAPR) performance comparable to that of the conventional OFDM system. Based on the results, the suggested f-OFDM system is considered a promising candidate for 5G and beyond systems.